Rút gọn biểu thức
----- Nội dung ảnh -----
Bài 11: Rút gọn biểu thức \( P = \frac{\sqrt{y} - \sqrt{x}}{\sqrt{xy - x} - \sqrt{y}} \)
Bài 12: Rút gọn biểu thức \( P = \frac{\sqrt{x} - 3}{x + 3\sqrt{y}} \)
Bài 13: Rút gọn biểu thức \( P = \left( \frac{\sqrt{\sqrt{x} - 1}}{\sqrt{x} + \sqrt{y}} \right) (x - y) \)
Bài 14: Rút gọn biểu thức \( P = \frac{1}{x + \sqrt{x} + 1} \)
Bài 15: Rút gọn biểu thức \( P = \frac{2\sqrt{x} - 1}{1 - x} \)
Bài 16: Cho biểu thức \( P = \frac{x - 1}{\sqrt{x^2 + 2} - 2 - 5\sqrt{x}} \)
a) Rút gọn \( P \)
b) Tính giá trị của \( P \) với \( x = \frac{2}{2 - \sqrt{3}} \)